2020
DOI: 10.3989/mc.2020.09319
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue performance evaluation of bitumen mastics reinforced with polyolefins through a dissipated energy approach

Abstract: Polymers are known to improve the fatigue resistance of sphalt mastics. However, undesirable results can be obtained if the polymer is not successfully integrated into the bitumen binder. The goal of this work is to evaluate the effect of the addition of three selected polyolefins on their mastic’s fatigue performance. Low and high density polyethylenes (LDPE and HDPE) and polypropylene (PP) were chosen and used at the concentration of 4 wt.%. A dissipated energy approach was used in order to analyze the fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The images taken by the fluorescence microscope can only capture the random spot of the polyolefinic structure that emerges on the surface of the sample. The lower absorption of bitumen components of PP is in agreement with previous results and it is related to the higher melt viscosity at the mixing temperature 69 …”
Section: Resultssupporting
confidence: 92%
“…The images taken by the fluorescence microscope can only capture the random spot of the polyolefinic structure that emerges on the surface of the sample. The lower absorption of bitumen components of PP is in agreement with previous results and it is related to the higher melt viscosity at the mixing temperature 69 …”
Section: Resultssupporting
confidence: 92%
“…The 0.7 wt% CNF-U oleogel results (not shown) led to the same conclusion. It seems that 200 Pa provoked a more severe disruption to the nanofibers network, which would have rearranged in a more favorable disposition when the material returned to its LVE regime [28]. This situation did not occur at higher nanofiber concentration because the network was probably too dense so as to enable further rearrangements.…”
Section: Cnf Oleogels' Response To "Rheo-destruction" and "Rheo-recov...mentioning
confidence: 99%
“…The virgin PE used was blended at 1300 rpm for 60 min in a preheated base binder at 160 C. Recycled plastic waste-modified asphalt was investigated in Saudi Arabia and observed that PE between 3 and 5% was optimum [ 136 ]. Roman et al [ 137 ] examined the low-density polyethylene (LDPE), high-density polyethylene (HDPE) and polypropylene (PP)-modified bitumen under strain and stress control experiment. From their results, it was observed that PP-modified bitumen showed the lowest fatigue resistance while LDPE, had the highest at 4 wt %.…”
Section: Polymers and Polymeric Bitumenmentioning
confidence: 99%